Exploration of the Stanford Integrated Psychosocial Assessment for Transplantation With Psychosocial and Medical Outcomes in Kidney and Kidney–Pancreas Transplant Recipients. (September 2019) - Chen, Gloria; Bell, Cynthia S.; Loughhead, Penelope; Ibeche, Bashar; Bynon, John S.; Hall, David R.; De Golovine, Aleksandra; Edwards, Angelina; Dar, Wasim A.
Introduction: The Stanford Integrated Psychosocial Assessment for Transplantation (SIPAT) is a psychometric instrument designed to assess patient risk for transplant. We investigated the association between SIPAT scores and demographic data with psychosocial and medical outcomes within a diverse kidney/kidney–pancreas transplant population. Design: The SIPAT was administered to all pretransplant candidates. A retrospective review of transplanted patients who had at least 6 months of follow-up was completed. Results: The sample included 136 patients: male (n = 77 [57%]) with a mean age of 47 years old. Thirty-eight percent were black (n = 51), 55% had less than a high school education (n = 74), and 65% had low socioeconomic status (n = 89). Statistical difference was found among SIPAT scores and substance use and support system instability ( P = .035, P = .012). Females ( P = .012) and patients with a history of psychopathology ( P = .002) developed or had a relapse of psychopathology following transplant. Patients with more than a high school education ( P = .025) and who were less than 30 years ( P = .026) had higher rejection incidence rates. Risk factors for rehospitalizations included Hispanic race, diabetes, and low socioeconomic status ( P = .036, P = .038, P = .014). African American/Black and male patients had higher incidence of infection events ( P = .032, P = .049). Mortality and treatment nonadherence were not significantly associated with SIPAT scores or demographic variables. Conclusion: The SIPAT was associated with posttransplant substance use and support system instability, while demographic variables were associated with the development and/or relapse of psychopathology, graft loss, rejection, infection events, and medical rehospitalizations. Revision of the SIPAT to include additional demographic components may lend to improved prediction of transplant outcomes.